Sifat Mekanik Komposit Serat Pelepah Kelapa Sawit sebagai Penguat Komposit Terhadap Kekuatan Tarik dan Impak - Satria Uji Perdana; Sri Hastuti; Ikhwan Taufik (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Palm fronds are solid waste from oil palm plantations that contain a lot of natural fibers. One of the utilization efforts that can be done is to optimize palm frond fiber waste into composite materials. The use of natural fiber mixtures in composites has produced stronger materials, which can serve as alternative materials for car bumpers. This research was conducted with the aim of knowing the value of impact toughness, tensile strength, and the type of failure that occurs in the fracture cross section. In this study, composites were made using palm frond fibers and polyester resin. The volume fraction variation applied is 30% fiber and 70% matrix with fiber lengths of 20 mm, 40 mm, and 60 mm. Impact toughness testing refers to ASTM E23 standard and tensile strength testing refers to ASTM D638 standard. The impact toughness value obtained in the 20 mm variation was 0.0065 J/mm², 40 mm was 0.0108 J/mm², and the 60 mm variation had the highest value of 0.0164 J/mm². The tensile strength value obtained in the 20 mm variation is 6.18 MPa, the 40 mm variation is 8.26 MPa, and the 60 mm variation has the highest value of 16.45 MPa. Analysis of the fracture cross section is categorized as a splitting fracture in multiple areas and the fracture cross section also shows the occurrence of fiber pull out after the fracture.